Biocidal effect of «barbasco» Lonchocarpus utilis (Smith,1930) as regulator of mosquitoes larvae - Mariños, Carlos (2004)
Seven bioassays in laboratory were carried out in order to evaluate the biocidal capacity of Lonchocarpus utilis (Smith,1930) «barbasco» on 7000 larvae of third and fourth stage of Anopheles benarrochi (Gabaldon,1941), main vector of malaria in Yurimaguas and Loreto. The biocidal activity was probed with two types of quality water. Fresh roots of L. utilis were processed by Vílchez (1993) methodology, it was obtained a fined powder which contains as active ingredient the rotenone. The biocidal activity was measured with 5 doses of powder of the root diluted in distilled water: 6,25; 3,1; 2,1 ; 1,0 and 0,15 g/L. It was used 1 mL of the homogenized as inoculum for dose. Readings were made hourly until the 24 hours post treatment to determine the effectiveness and susceptibility. At the 12 hours post-treatment the doses of 6,25 and 3,1 g/L, obtained 98 and 89% of larval mortality when it was utilized in distilled water and in water of breeding site mortality was of 86 and 82% respectively. At the 24 hours mortality reached 99 and 94% using distilled water and with water of breeding site was 93 and 90%. At the 6 hours of exposure with distilled water, the medium lethal dose (DL50) was of 0,63 g/ L and the lethal dose ninety (DL90) it was of 12,44 g/L; while at the 12 hours the DL50 was of 0,48 g/ L and the DL90 was 7,23 g/L. Utilizing breeding site water at the 6 hours, the DL50 was of 1,36 g/L and the DL90 it was 27,58 g/L; while at the 12 hours the DL50 was 0,83 g/L and DL90 it was of 9,83 g/L of the extract raw of L. utilis on the larvaes. The results made it possible to verify the effectiveness of the raw extract of L. utilis on larvae of A. benarrochi as potential larvicide and its action is influenced by the water quality and the dose of application.